2008
DOI: 10.1074/jbc.m704332200
|View full text |Cite
|
Sign up to set email alerts
|

Modest PGC-1α Overexpression in Muscle in Vivo Is Sufficient to Increase Insulin Sensitivity and Palmitate Oxidation in Subsarcolemmal, Not Intermyofibrillar, Mitochondria

Abstract: PGC-1␣ overexpression in skeletal muscle, in vivo, has yielded disappointing and unexpected effects, including disrupted cellular integrity and insulin resistance. These unanticipated results may stem from an excessive PGC-1␣ overexpression in transgenic animals. Therefore, we examined the effects of a modest PGC-1␣ overexpression in a single rat muscle, in vivo, on fuel-handling proteins and insulin sensitivity. We also examined whether modest PGC-1␣ overexpression selectively targeted subsarcolemmal (SS) mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
237
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 198 publications
(257 citation statements)
references
References 77 publications
18
237
1
1
Order By: Relevance
“…Viewed in this light, PGC-1α-induced insulin resistance in transgenic mice is less of a paradox than has been suggested [11]. Recently, we showed that inducing a modest increase in PGC-1α protein, based on physiological and metabolic considerations, has an insulin-sensitising effect in healthy muscle [3]. Nevertheless, some very critical questions remain unanswered, e.g.…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations
“…Viewed in this light, PGC-1α-induced insulin resistance in transgenic mice is less of a paradox than has been suggested [11]. Recently, we showed that inducing a modest increase in PGC-1α protein, based on physiological and metabolic considerations, has an insulin-sensitising effect in healthy muscle [3]. Nevertheless, some very critical questions remain unanswered, e.g.…”
Section: Introductionmentioning
confidence: 80%
“…Muscle fibre composition of muscles in lean and obese animals was determined as described by us recently [3], by staining serial cross sections (10 µm) for myofibrillar ATPase and succinate dehydrogenase, from which we determined their physiological and metabolic characteristics [3].…”
Section: Descriptive Characteristics Of Lean and Obese Zucker Ratsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have reported that expression of PGC-1a is upregulated by prolonged exercise in rats 31 and that moderate PGC-1a overexpression in rat skeletal muscle in vivo improves insulin sensitivity. 32 Future investigations could address whether prolonged exercise combined with nifedipine treatment could synergistically elevate PGC-1a mRNA levels and improve insulin sensitivity in patients with obesity and/or type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%